Polyaniline blends, composites, and nanocomposites - P. M., Visakh; Della Pina, Cristina; Falletta, Ermelinda (Elsevier, 2018)
"Polyaniline Blends, Composites, and Nanocomposites summarizes recent advances in polyaniline-based blends, composites and nanocomposites. Polyaniline (PANI) is a conducting polymer with a range of potential applications, particularly in electronics and packaging. The book covers the preparation, characterization and application of PANI-based composites, including the structure-property relationship and modification of PANI. Offers an in-depth update on the major findings and observations in the field of polyaniline-based blends, composites and nanocomposites, with contributions from leading researchers in industry, academia, government and private research institutions worldwide. An application-oriented, practical guide to the development and application of this polymeric material. The book includes discussion of reinforcement of polyaniline via addition of carbon-based materials, blends with thermoplastics, thermosets, natural and synthetic rubber, and polyaniline based composites and nanocomposites, with an emphasis on enabling polymer scientists and engineers to more effectively utilize this material in new applications. Includes an in-depth update on the state of research into this exciting material, with detailed and practical information for developing emerging applications of polyanilineEnables polymer scientists and engineers to overcome challenges and take advantage of opportunities relating to polyaniline, e.g., solubility of the polymer, improving conductivity and moreIncludes detailed coverage of the preparation, characterization and application of PANI-based composites in detail, along with the structure-property relationship and modification of PANI"--